1992
DOI: 10.1021/ie00001a026
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling substituent and solvent effects during hydrolysis of substituted anisoles in supercritical water

Abstract: The kinetics of hydrolysis in supercritical water of a series of substituted anisoles to methanol and the corresponding substituted phenol probed the coupling of solvent and substituent effects. For supercritical water concentrations [H20] 5 3 mol/L, the substituent effects exhibited compelling correlation according to the classic Hammett formalism. For [H20] > 5 mol/L, however, the Hammett correlation had an internal minimum at cr = 0, indicative of rate acceleration by both electronwithdrawing and electron-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 15 publications
3
53
0
1
Order By: Relevance
“…13 The three state points considered were all at T ) 380°C (T r ) 1.01), but included a range of pressures from 23.2 to 49 MPa. The measured rate constant for hydrolysis, k 1 , is shown in Table 2 along with k p , the rate constant for the competing pyrolysis pathways.…”
Section: Hydrolysis Of Anisolementioning
confidence: 99%
See 2 more Smart Citations
“…13 The three state points considered were all at T ) 380°C (T r ) 1.01), but included a range of pressures from 23.2 to 49 MPa. The measured rate constant for hydrolysis, k 1 , is shown in Table 2 along with k p , the rate constant for the competing pyrolysis pathways.…”
Section: Hydrolysis Of Anisolementioning
confidence: 99%
“…In particular, it has been found that for low pressures homolytic free radical mechanisms dominate, whereas for high pressures more chemically selective heterolytic, ionic mechanisms dominate. 3,13 This variation in reaction process with pressure is known to be tied to the large variation in SCW's density, and thus its dielectric properties, with pressure in this regime. [2][3][4][14][15][16] For example, at 380°C, the dielectric constant of water varies from ) 2 at P ) 21 MPa to ) 14 at P ) 47 MPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Subsequently, we applied our compressible continuum (CC) model to this reaction system and found that this model provides a much better description of the pressure dependence of the reaction rate when compared to experiment. 11,37,39 However, the experimental data are extremely limited, providing only the rate constant at three different pressures. 11,40 Thus, no check on the detail of the CC calculationsssolvent density distributions and absolute differentials in solvation energy along the reaction pathscould be made.…”
Section: Introductionmentioning
confidence: 99%
“…11,37,39 However, the experimental data are extremely limited, providing only the rate constant at three different pressures. 11,40 Thus, no check on the detail of the CC calculationsssolvent density distributions and absolute differentials in solvation energy along the reaction pathscould be made. 37 Johnston and Rossky and co-workers have provided a more detailed demonstration of the failure of the IC model by comparing results from this model against computer simulation.…”
Section: Introductionmentioning
confidence: 99%